Section Preequating Under the Equivalent Groups Design Without IRT. Issue 3 (September 2014) - Guo, Hongwen; Puhan, Gautam
<x xml:space="preserve">Abstract</x> In this article, we introduce a section preequating (SPE) method (linear and nonlinear) under the randomly equivalent groups design. In this equating design, sections of Test X (a future new form) and another existing Test Y (an old form already on scale) are administered. The sections of Test X are equated to Test Y, after adjusting for the imperfect correlation between sections of Test X, to obtain the equated score on the complete form of X. Simulations and a real‐data application show that the proposed SPE method is fairly simple and accurate.